Surgical treatment of multiple and concomitant injuries - F. I. Ibragimov; N. A. Kasumov (Вестник хирургии имени И.И. Грекова)
The objective of the study was to conduct a comparative analysis of the results of traditional and modern methods of surgical treatment of patients with severe concomitant injury, accompanied by fractures of the tubular bones of the limbs.Material and methods. The retro-and prospective analysis of the results of surgical treatment of 1033 patients with severe concomitant injury hospitalized in Baku Clinical Hospital № 3 for the period from 2009 to 2015 is presented. The patients were divided into 2 groups for a comparative evaluation of the results of treatment, depending on the effectiveness of the applied medical tactics. The 1st (main) group consisted of 828 (80.2 %) patients who were treated using the tactics of programmed multi-stage surgical treatment in accordance with the concept of «damage control». The 2nd (comparison group) included 205 (19.8 %) patients, who were treated using the traditional tactics of surgical treatment.Results. In a multi-field General surgical hospital, the introduction of the «damage control» program using the tactics of programmed surgical treatment in patients with severe concomitant and multiple injury allowed to increase surgical activity and reduce the mortality rate from 45.9 to 21.6 %.Conclusion. The application of tactics of stage surgical correction of injuries allows to improve the immediate results of treatment of patients with severe concomitant and multiple injury.